MELITO'S HOMILY ON THE PASSION: AN INVESTIGATION INTO THE SOURCES OF BYZANTINE HYMNOGRAPHY - Wellesz, E. J. (The journal of theological studies, 1943)
E. J. WELLESZ; MELITO'S HOMILY ON THE PASSION: AN INVESTIGATION INTO THE SOURCES OF BYZANTINE HYMNOGRAPHY, The Journal of Theological Studies, Volume os-XLIV, I